Narratives of Developing Authentic Assessment Instruments for Islamic Religious Education in Secondary Schools Through a Participatory ADDIE Approach - Susanna Susanna; Jamaluddin Idris; Zainal Abidin (International Journal of Educational Narratives, 2026)
Background. Authentic assessment has become a central component of the Merdeka Curriculum implementation in Indonesia, particularly in Islamic Religious Education (PAI), which emphasizes holistic student development across cognitive, affective, and psychomotor domains. Purpose. This study aimed to develop a valid and practical participatory-based module for developing authentic assessment instruments in secondary school PAI learning through the integration of the ADDIE model and participatory professional collaboration within the MGMP forum. Method. This study employed a Research and Development (R&D) design using the ADDIE model consisting of Analysis, Design, Development, Implementation, and Evaluation phases. The research involved 35 PAI teachers from 23 senior secondary schools in Nagan Raya Regency, Aceh Province. Results. The findings revealed that the developed module achieved an average expert validity score of 85% categorized as Very Valid and an average practicality score of 80% categorized as Practical. The participatory mechanism implemented through structured FGDs effectively positioned teachers and supervisors as active co-constructors in developing authentic assessment instruments that were contextual, relevant, and applicable to classroom practice. Conclusion. The integration of the ADDIE model with a participatory approach provides an effective framework for developing authentic assessment competencies among PAI teachers.